Strategi Pemasaran untuk Meningkatkan Loyalitas Pelanggan melalui Marketing Mix 7P dalam Perspektif Bisnis Syariah (Studi Kasus: Sanjai Saiyo di Kecamatan Harau Kabupaten Lima Puluh Kota) - Jingga Silvia; Nini Sumarni; Yenty Astarie Dewi; Dewi Manda Angraini (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
The increasing competition among micro, small, and medium enterprises (MSMEs) in the culinary sector has led to fluctuating sales and challenges in maintaining customer loyalty, particularly for local specialty food businesses such as Sanjai Saiyo in Harau District, Lima Puluh Kota Regency. This study aims to analyze the implementation of the marketing mix 7P in enhancing customer loyalty from a Sharia business perspective. A qualitative case study approach was employed, using data collected through observations, in-depth interviews with business owners, customers, and local community members, as well as documentation. The data were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that the consistent application of the 7P elements product quality, fair pricing, strategic location, honest promotion, ethical human resources, transparent processes, and adequate physical evidence aligned with Sharia principles such as honesty, justice, and accountability, contributes significantly to building trust and encouraging repeat purchases. This integration not only strengthens customer loyalty but also supports sustainable business practices for MSMEs.